Dinamika reog ponorogo sebagai simbol identitas lokal dan nasional di era globalisasi - Azela, Imelda Nur (Maliki Interdisciplinary Journal, 2025)
Reog Ponorogo is one of the traditional performing arts that reflects the cultural identity of the people of Ponorogo, East Java. Over time, Reog has not only functioned as a local symbol, but has also been raised as a representation of national culture. However, the impact of globalization has presented major challenges to the existence and values of Reog culture. Tthis article examines the dynamics of Reog Ponorogo as a symbol of local and national identity in facing the challenges of the global era. Using a qualitative approach and literature study, this study reveals that despite changes in from and meaning, Reog still plays an important role in maintaining the identity of the Indonesian nation. The use of technology in performances, such as multimedia or digital adaptations, can attract the attention of many audiences without reducing the essence of tradition. In addition, strengthening the local arts community is crucial for the sustainability of Reog. The government and related institutions need to provide more support for Reog artists through training, performance facilities, and the creation of creative spaces.